2014
DOI: 10.1186/2050-7283-2-11
|View full text |Cite
|
Sign up to set email alerts
|

Mood and cognition in healthy older European adults: the Zenith study

Abstract: BackgroundThe study aim was to determine if state and trait intra-individual measures of everyday affect predict cognitive functioning in healthy older community dwelling European adults (n = 387), aged 55-87 years.MethodsParticipants were recruited from centres in France, Italy and Northern Ireland. Trait level and variability in positive and negative affect (PA and NA) were assessed using self-administered PANAS scales, four times a day for four days. State mood was assessed by one PANAS scale prior to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 108 publications
(137 reference statements)
4
15
0
Order By: Relevance
“…working memory [13], visual spatial search [12], attention [11]), and decreased cognitive ability with increasing attachment to one's phone [14,16,26]. Further, past studies have demonstrated the effect of affective state on cognitive performance [19,20,[22][23][24][25]27]. To…”
Section: Present Studymentioning
confidence: 99%
See 2 more Smart Citations
“…working memory [13], visual spatial search [12], attention [11]), and decreased cognitive ability with increasing attachment to one's phone [14,16,26]. Further, past studies have demonstrated the effect of affective state on cognitive performance [19,20,[22][23][24][25]27]. To…”
Section: Present Studymentioning
confidence: 99%
“…The researchers attributed positive affect in participants' improved controlled cognitive processing and less inhibitory control. On the other hand, participants' negative affect had fewer spatial working memory errors [23] and higher cognitive failures [25]. Yet, in all of these studies-the direction of modulation, intensity, valence of experiencing a specific affective state ranged widely and primarily driven by external stimuli (i.e.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…They used the same data set as the current study, but different outcome measurements and only looked at the outcome at baseline. Another study with older adults showed that PA predicted greater sustained attention, but did not find effects of PA on recognition memory, spatial working memory, and reaction time (Simpson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…One cross‐sectional study showed that higher PA was associated with better free memory recall in the older (65 to 82 years) age group (Hill et al, ). Another study showed that PA predicted greater sustained attention in older adults (Simpson et al, ). In both studies, the contribution of PA to the proportion of variance explained was small (1–3%).…”
Section: Introductionmentioning
confidence: 99%